Burnout Perawat Rumah Sakit di Masa Pendemi Covid 19 Ditinjau dari Beban Kerja dan Dukungan Keluarga - Rika Damayanti; Rahmad Purnama; Nur Izam Zamzami; Hamid Mukhlis (Universitas Aisyah Pringsewu, 2022)
Burnout is a condition in which individuals experience physical, mental and emotional exhaustion caused by long-term stress and situations that require the individual to experience a high level of emotional attachment. This study aims to determine the relationship between family support and workload with a burnout in Abdul Moeloek General Hospital nurses. The hypothesis proposed is that there is a positive relationship between family support and workload with a burnout in Abdul Moeloek General Hospital nurses. The subject of this research is Abdul Moeloek General Hospital nurses. The sample in this study was 66 people. The sampling technique used was purposive random sampling. The research data were collected using the Burnout Scale. Family Support Scale. Workload Scale. The Burnout scale consists of 16 valid items with a reliability coefficient of 0.757. The Family Support Scale consists of 21 valid items with a reliability coefficient of 0.885. The Workload Scale consists of 25 valid items with a reliability coefficient of 0.880. Data analysis using multiple regression analysis techniques. The results of the first study were Rx1.2y = 0.669, F = 5.539 and p = 0.000 (p less than 0.01). This means that there is a positive relationship between family support and workload with a burnout in Abdul Moeloek General Hospital nurses. Family support and workload provide an effective contribution of 44.8%. The second result with rx1-y=-0,531 and R2=0,282 and p=0,000 (p less than 0,01). Which shows a significant negative relationship between family support and burnout of nurses in Abdul Moeloek General Hospital. The third result is rx2-y=0,574 and R2=0,323 and p=0,000 (p less than 0,01). Which shows a significant positive relationship between workload and burnout of nurses in Abdul Moeloek General Hospital. Abstrak: Burnout merupakan suatu kondisi dimana individu mengalami kelelahan fisik, mental dan emosional yang disebabkan oleh stres dalam jangka waktu yang lama serta situasi yang menuntut individu tersebut put mengalami adanya keterikatan emosional yang cukup tinggi. Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan keluarga dan beban kerja dengan burnout pada perawat Rumah Sakit Umum Abdul Moeloek. Hipotesis yang diajukan adalah ada hubungan yang positif antara dukungan keluarga dan beban kerja dengan burnout pada perawat Rumah Sakit Umum Abdul Moeloek Subjek Penelitian ini adalah perawat Rumah Sakit Umum Abdul Moeloek. Sampel dalam penelitian ini adalah 66 orang. Teknik pengambilan sampel dengan menggunakan purposive random sampling. Data penelitian dikumpulkan dengan Skala Burnout. Skala Dukungan Keluarga. Skala Beban Kerja. Skala Burnout terdiri dari 16 aitem valid dengan koefisien reliabilitas 0,757. Skala Dukungan Keluarga terdiri dari 21 aitem valid dengan koefisien reliabilitas 0,885. Skala Beban Kerja terdiri dari 25 aitem valid dengan koefisien reliabilitas 0,880. Analisis Data menggunakan teknik analisis regresi berganda. diperoleh hasil penelitian pertama Rx1.2y = 0,669 nilai F=5,539 dan p=0,000 (p kurang dari 0,01). Hal ini berarti ada hubungan yang positif antara dukungan keluarga dan beban kerja dengan burnout pada perawat Rumah Sakit Umum Abdul Moeloek. Dukungan keluarga dan beban kerja memberikan sumbangan efektif sebesar 44,8%. Hasil kedua dengan rx1-y=-0,531 dan R2=0,282 dan p=0,000 (p kurang dari 0,01). Yang menunjukkan hubungan negatif signifikan antara dukungan keluarga dengan burnout pada perawat Rumah Sakit Umum Abdul Moeloek. Hasil ketiga dengan rx2-y=0,574 dan R2=0,323 dan p=0,000 (p kurang dari 0,01). Yang menunjukkan hubungan positif signifikan antara beban kerja dengan burnout pada perawat Rumah Sakit Umum Abdul Moeloek.